1999
DOI: 10.1111/j.1469-7793.1999.515ae.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of rhythmically active cells in guinea‐pig stomach

Abstract: Many organs containing smooth muscle are myogenically active. This was assumed to originate from activity within the individual smooth muscle cells. Some smooth muscle cells have low resting membrane potentials and generate myogenic activity, in much the same way as cardiac pacemaker cells, through the sequential activation of voltage-dependent ion channels (see for example Anderson, 1993). In others, myogenic activity originates from the cyclic release of calcium ions (Ca¥) from stores inside the smooth muscl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

41
497
1

Year Published

1999
1999
2011
2011

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 285 publications
(539 citation statements)
references
References 43 publications
41
497
1
Order By: Relevance
“…Effect of caffeine on regenerative potentials, membrane noise and unitary potentials recorded from single bundles of circular muscle from the antral region of guinea-pig stomach It has previously been shown that low concentrations of caffeine abolish both regenerative potentials and the secondary component of slow waves (Dickens et al 1999). In this series of experiments we examined the effects of low concentrations of caffeine on regenerative potentials and membrane noise and on unitary potentials detected in preparations that had been pretreated with BAPTA AM (10-20 ìÒ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Effect of caffeine on regenerative potentials, membrane noise and unitary potentials recorded from single bundles of circular muscle from the antral region of guinea-pig stomach It has previously been shown that low concentrations of caffeine abolish both regenerative potentials and the secondary component of slow waves (Dickens et al 1999). In this series of experiments we examined the effects of low concentrations of caffeine on regenerative potentials and membrane noise and on unitary potentials detected in preparations that had been pretreated with BAPTA AM (10-20 ìÒ).…”
Section: Resultsmentioning
confidence: 99%
“…When caffeine (1 mÒ) was added to the physiological saline, the primary components of the slow waves persisted at low frequency ( Fig. 11B; see also Dickens et al 1999). These preparations had input resistances in the range 0·9-1·7 MÙ (1·4 ± 0·2 MÙ).…”
Section: ------------------------------------------------------------mentioning
confidence: 99%
See 1 more Smart Citation
“…I n the stomach, electrical slow waves are generated by a specialized network of cells, known as interstitial cells of Cajal (ICC) , located in the myenteric region between the circular and longitudinal muscle layers (ICC-MY) (1)(2)(3). The stomach has a continuous network of ICC-MY from the orad corpus to the pyloric sphincter (1), and samples of muscle removed from each region demonstrate spontaneous activity that is characteristic of pacemaker cells in that region (4).…”
mentioning
confidence: 99%
“…The slow waves originate in the ICCs distributed in the GI tract (Dickens et al, 1999;Huizinga et al, 1995;Langton et al, 1989;Torihashi et al, 1995;Ordog et al, 1999;Ward et al, 1994). ICCs express c-kit immunoreactivity and form gap junctional connections with ICCs and with smooth muscle cells (Huizinga et al, 1997;Komuro et al, 1992;Sanders, 1996).…”
Section: Discussionmentioning
confidence: 99%